First Detection of the CTXM-15 Producing Escherichia coli O25-ST131 Pandemic Clone in Ecuador (2019)
Our aim was identify of the pandemic B2-ST131 Escherichia coli clone by to the Institute Pasteur and Achtman scheme, and investigate the resistance profile phenotypic-genotypic, with identification of class 1 integron. Of thirty-five ESBL-producing isolates recovered of patients with diagnosis of urinary tract infections (UTI), six E. coli strains serotype O25 were identified with resistance antimicrobial to several groups of antibiotics such as broad-spectrum cephalosporins, fluoroquinolones and aminoglycosides, harboring blaSHV, blaCTX-M genes in all isolates and blaTEM in two isolates. Sequencing of blaCTX-M revealed CTX-M-15 in all strains. The PMQR aac(6’)-Ib-cr and qnrB19 genes were presented in five and four isolates respectively, AMEs genes aac(6’)-Ib and aac(3)-IIa were presented in strain amikacin-gentamicin-resistant. Sequencing of the variable regions of the class 1 integron revealed dfrA and aadA genes cassette. The analysis of multilocus sequence typing (MLST) confirms the presence of the pandemic B2-ST131 E. coli clone by Achtman scheme in all ST43 isolates obtained by of the Institute Pasteur scheme. The results presented herein, reveal the presence of B2-ST131 E. coli clone in Ecuador, disseminated in hospitals and community settings.